Managing Extension of Time (EOT) in B2B Construction: From Contractual Mechanisms to Relational Governance for Dispute Prevention - Augustinus Setijanto; Sarwono Harjomuljadi (LPPM of NAROTAMA UNIVERSITY, 2026)
Extension of Time (EOT) is one of the most important mechanisms in construction contracts because it serves to regulate adjustments to the project schedule when delays occur. However, in Business-to-Business (B2B) construction projects, EOT is often narrowly understood as merely the right to additional time or even directly associated with cost claims. This reductive understanding frequently triggers conflicts, as the parties fail to distinguish between the right to time, the right to compensation, and the quality of the relationship that underpins contract execution. This article aims to build a more comprehensive understanding of EOT by situating it within three main dimensions: the contractual dimension, the economic dimension, and the relational dimension. This study employs a qualitative method with conceptual, normative, and analytical approaches, through an examination of construction contract literature, institutional economics theory, relational contract theory, dispute avoidance, and a critical analysis of high-rise project practices. The findings indicate that EOT is fundamentally a mechanism for allocating time-related risks, not an automatic basis for financial compensation. Compensation arises only when there is a clear basis of liability and a provable causal relationship. Furthermore, construction disputes are more often triggered not by the delay itself, but by communication failures, weak documentation, misclassification of delays, and poor quality of relationships between parties. Therefore, this article argues that EOT needs to be reframed from merely a claim tool into an instrument of relational governance to prevent disputes, build trust, and create shared value in B2B construction projects.